Ocular injectable formulation assessment for oxidized dextran-based hydrogels - Maia, João (2009)
Initiator-free injectable hydrogels are very interesting for drug and/or cell delivery applications, since they can be administered in a minimally invasive way, and avoid the use of potentially harmful chemical initiators. In the current work, oxidized dextran crosslinked with adipic acid dihydrazide hydrogels were further characterized and tuned to produce formulations, with the aim of producing an injectable formulation for the possible treatment of posterior eye diseases. The gelation rate and the hydrogel dissolution profile were shown to be dependent on the balance between the degree of dextran oxidation, and the concentration of both components. For the in vitro studies, rabbit corneal endothelial cells were seeded on the hydrogels to assess cytotoxicity. Hydrogels prepared with low oxidized dextrans were able to promote cell adhesion and proliferation to confluence in just 24 h, while more highly oxidized samples promoted cell adhesion and proliferation, but without achieving confluence. Cell viability studies were performed using MTS assays to verify the non-cytotoxicity of hydrogels and their degradation byproducts, rendering these formulations attractive for further in vivo studies.